2015
DOI: 10.3390/socsci4020421
|View full text |Cite
|
Sign up to set email alerts
|

Citations and Convictions: One Community’s Coordinated Response to Intimate Partner Violence & Efforts toward Offender Accountability

Abstract: In 1996, a coordinated community response (CCR) was formally established in a mid-sized Midwestern city to improve the criminal justice response to intimate partner violence (IPV). Data for this study included all IPV-related incidents to which the local police department responded since the establishment of the CCR for a fourteen year period. Effective CCRs provide for IPV offender accountability through citation and prosecution of IPV-related crimes. Concerns about demographic variables affecting citation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…They also provide opportunities for improved communication among stakeholders, cross-training, referral facilitation, and an avenue to address weaknesses or gaps in service provision ( Office of Violence Against Women, 2016 ). Research has shown that CCRTs are more effective when they are interdisciplinary and integrated throughout the community ( Beldin et al, 2015 ; DePrince et al, 2012 ; Family Justice Center Alliance, 2013 ).…”
mentioning
confidence: 99%
“…They also provide opportunities for improved communication among stakeholders, cross-training, referral facilitation, and an avenue to address weaknesses or gaps in service provision ( Office of Violence Against Women, 2016 ). Research has shown that CCRTs are more effective when they are interdisciplinary and integrated throughout the community ( Beldin et al, 2015 ; DePrince et al, 2012 ; Family Justice Center Alliance, 2013 ).…”
mentioning
confidence: 99%